Rationale and Design of the Dapagliflozin Effect on Cardiovascular Events in Acute Heart Failure (DAPA ACT HF)-TIMI 68 Trial - Berg, David D; Patel, Siddharth M; Haller, Paul M; Bělohlávek, Jan; Desai, Akshay S; Drożdż, Jarosław; Inzucchi, Silvio E; McMurray, John J V; Merkely, Béla; O'Meara, Eileen; Verma, Subodh; Cange, Abby L; et al. (JACC. Heart failure, 2025)
Although sodium-glucose cotransporter 2 inhibitors reduce the risk of cardiovascular death or worsening heart failure (HF) in patients with chronic HF, there are limited data on initiation in hospitalized patients with HF. DAPA ACT HF-TIMI 68 (Dapagliflozin and Effect on Cardiovascular Events in Acute Heart Failure - Thrombolysis in Myocardial Infarction 68) is an international, randomized, double-blind trial evaluating the initiation of dapagliflozin (10 mg daily) vs placebo in 2,401 patients hospitalized for acute HF. Patients were enrolled irrespective of left ventricular ejection fraction, type 2 diabetes status, or chronicity of HF (de novo and worsening chronic HF). Randomized participants receive blinded treatment for 2 months. The primary efficacy endpoint is time to first occurrence of cardiovascular death or worsening HF (worsening HF during the index admission, rehospitalization for worsening HF, or urgent HF visit). Key safety endpoints include symptomatic hypotension and worsening kidney function. This is the first cardiovascular outcomes trial designed specifically to evaluate the efficacy and safety of in-hospital initiation of dapagliflozin in patients hospitalized for the management of acute HF. (Dapagliflozin and Effect on Cardiovascular Events in Acute Heart Failure - Thrombolysis in Myocardial Infarction 68 [DAPA ACT HF-TIMI 68]; NCT04363697; EudraCT # 2022-001262-35).
Keywords: senioři; dvojitá slepá metoda; Stroke Volume; glukosidy; multicentrické studie jako téma; Glucosides; hospitalization; Benzhydryl Compounds; Sodium-Glucose Transporter 2 Inhibitors; Double-Blind Method; Multicenter Studies as Topic; clinical trial; worsening heart failure; výsledek terapie; benzhydrylové sloučeniny; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; diabetes mellitus 2. typu; tepový objem; ženské pohlaví; Randomized Controlled Trials as Topic; Humans; sodium-glucose cotransporter 2 inhibitors; Acute Disease; glifloziny; srdeční selhání; lidé středního věku; Hospitalization; akutní nemoc; hospitalizace; randomizované kontrolované studie jako téma; Female; Aged; Treatment Outcome; Heart Failure; lidé; Male